ESC-Leitlinien zum Vorhofflimmern 2016: Zusammenfassung der wichtigsten Empfehlungen und Neuerungen = ESC guidelines on atrial fibrillation 2016 : summary of the most relevant recommendations andmodifications - Eckardt, Lars; Borggrefe, Martin (Herz, 2016)
The first European Society of Cardiology (ESC) guidelines on atrial fibrillation (AF) developed in collaboration with the European Association for Cardio-Thoracic Surgery (EACTS) were published in August 2016. These guidelines replace the revised guidelines from 2012 and contain some interesting new aspects. The topics range from the pathophysiology through diagnostics, therapy and stroke prevention up to special clinical situations, such as atrial fibrillation in cardiopathy, sport and pregnancy. Early screening, patient informed consent, individualized therapy and the modification of factors promoting atrial fibrillation are of particular importance. The guidelines recommend the establishment of AF heart teams, containing specialists from various disciplines. The guidelines also underline the importance of non-vitamin K‑dependent oral anticoagulants (NOAC) for stroke prevention compared to standard anticoagulants with vitamin K antagonists. For symptomatic and especially paroxysmal atrial fibrillation, the guidelines emphasize the importance of an antiarrhythmic treatment with catheter ablation and/or pharmaceutical antiarrhythmic therapy in addition to a frequency regulating therapy.